Adding insult to injury: A review of infections following envenomings - Dayle Leonard; Aoife Boyd; Michel M. Dugon (Toxicon: X, 2025)
Over 100 lineages of animal have evolved venom for a wide variety of purposes. An estimated 2.5 million people are bitten by snakes and another 1.2 million are stung by scorpions with many envenomings resulting in death. However, survival is not the end point of the envenoming syndrome as chronic life altering conditions, such as amputations, disfigurement and neuropathies can occur. In this context, infections at the site of envenomation could play an important role as they can exacerbate mortality and the incidence and severity of life altering conditions.This review assesses the connection between envenoming and infections. It summarises and highlights the literature describing cases of envenoming-mediated infection by various taxa and the circumstances of these envenomings and the outcomes of infection. It could be deduced that the risk factors for envenoming-led infections are multifactorial. Factors enhancing the risk of infection include; 1. The delivery system, with larger devices leading to more substantial wounds, 2. Venom composition, with venoms containing cytotoxins more commonly implicated in infections, and 3. The environment, with aquatic microbiomes and venom system microbiomes as sources of the pathogen species. Infections are difficult to diagnose due to symptoms synonymous with those of the envenoming and it is recommended that medical practitioners consider the possibility of infection throughout all stages of medical treatment. There is a notable gap in our understanding of envenoming-led infections and further research will help to increase patient survival.